Establishment and Competition of Native Forest Species in Araucaria angustifolia Stands with Different Coverage Degrees in Misiones, Argentina - Olguín, Flavia Yesica (2020)
Mixed plantations with native species are a viable tool to meet current wood production and conservation demands that can contribute to the restoration of degraded forests. In Misiones, Argentina, 30000 ha are destined to mono-specific plantations of the native Araucaria angustifolia (Bertol.) Kuntze, for timber purposes. The mixes with other native timber species in uneven-aged plantations have ecological advantages over monospecific stands because they increase biodiversity and complexity. In mixed plantations, competition depends on the availability of resources, but also on the requirements and ages of the trees.